DESAIN PEMBELAJARAN BERBASIS TEKNOLOGI AUGMENTED REALITY (AR) PADA PEMBELAJARAN DASAR TEKNIK PEMBUBUTAN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PEMECAHAN MASALAH - Nisaudzakiah Utami, - (2023)
Basic turning techniques are the main things that need to be mastered by Phase E Vocational School students who are taking a machining engineering expertise program. Basic turning techniques are subjects that require students to develop basic skills in turning work before producing. Currently teachers need to use learning media that can facilitate students to practice lathes directly. One of the technologies needed today is learning media based on Augmented Reality (AR). AR is a technology that transforms the virtual world into the real world. This AR will help students in using a lathe virtually. The purpose of this research is to create a learning design for lathe practice based on Augmented Reality (AR) technology that can improve students' critical thinking and problem solving. The research method used to design this learning design is Design Based Research (DBR). The model and development of the selected learning design is the Taba model. The results of the research have succeeded in developing a learning design for the basic material of AR-based turning techniques which can improve critical thinking skills and problem solving with the characteristics of having a syntax consisting of five phases of PjBL and discovery learning, each phase of which has independent learning activities with AR-based media. The five phases are as follows: 1) determining basic questions (giving stimulus and identifying problems), 2) designing project plans (data collection), 3) preparing schedules (data processing 1), 4) monitoring students (data processing 2), 5) Testing the results (Proof). The test results show that the design of learning designs further enhances critical thinking skills and problem solving which is evident in the results of the judgments of learning design experts who state that it is feasible based on the integrated learning model syntax criteria of indicators of critical thinking skills and problem solving. So that this learning design can be made into AR-based learning media.